PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI (Studi Kasus Pada Yayasan Sunan Kalijogo Jabung-Malang) - Nanda Prasetya Utama; Muhammad Mansur; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTWork effectiveness is one of the goals of job implementation. This can beachieved if the implementation of work in accordance with the requirementsrequired by the job. The purpose of this study is to determine whether there isinfluence of work motivation, and work discipline on the effectiveness ofemployees at Yayasan Sunan Kalijogo Jabung-Malang. The purpose of this studyis also to determine the extent to which the influence of work motivation, andwork discipline on the effectiveness of employees at Yayasan Sunan KalijogoJabung-Malang.The results of this study partially prove that the variable of work motivationdoes not have a significant effect on the effectiveness of employees with asignificance value of 0.075 or above 0.05 and has the lowest coefficient of 0.317,while the variable work discipline partially have a significant effect on theeffectiveness Employee work with a significance value of 0.007 or below 0.05 andhas a coefficient value above the motivation variable is 0.472.But simultaneously these two variables are very influential on theeffectiveness of employees at the Foundation Sunan Kalijogo Jabung Malang,because the value obtained F test of 9,253 with a significance level of 0,000 whichis smaller than 0.005. From the results of the analysis can be taken a conclusionthat the variables of work motivation, and work discipline have a positiveinfluence on the effectiveness of employee work on Yayasan Sunan KalijogoJabung-Malang. However, the work discipline variable is the dominant factorwhich has the greatest influence to the level of effectiveness of the employee'swork at Yayasan Sunan Kalijogo Jabung-Malang.Keywords: Work Motivation, Work Discipline and Work Effectiveness OfEmployees